2024
DOI: 10.3389/fntpr.2024.1347855
|View full text |Cite
|
Sign up to set email alerts
|

Vernonia amygdalina: a comprehensive review of the nutritional makeup, traditional medicinal use, and pharmacology of isolated phytochemicals and compounds

Sileshi Degu,
Asfaw Meresa,
Zelalem Animaw
et al.

Abstract: Vernonia amygdalina is a perennial shrub that belongs to the family Asteraceae. The herb is an indigenous African plant that grows in most parts of sub-Saharan Africa. It is probably the most used medicinal plant in the genus Vernonia. Previous studies on the traditional medicinal value, nutritional composition, classes of phytochemical or compound isolation, and evaluation of their pharmacology activity are numerous. This provokes us to review and provide up-to-date evidence-based information on the study pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…The leafy part of G. amygdalinum plays a crucial role in nutritional requirements for human health and food safety, as it contains sufficient concentrations of proximal composition, nutrients (proteins, minerals) and phytochemicals. 119 Several studies have also demonstrated its effectiveness in animal feed, with weight gains and interesting antibiotic activity. 120,121 However, there is little data on the production and economics of bitter leaf.…”
Section: Under-utilized Leafy Vegetables (Ulv)mentioning
confidence: 99%
“…The leafy part of G. amygdalinum plays a crucial role in nutritional requirements for human health and food safety, as it contains sufficient concentrations of proximal composition, nutrients (proteins, minerals) and phytochemicals. 119 Several studies have also demonstrated its effectiveness in animal feed, with weight gains and interesting antibiotic activity. 120,121 However, there is little data on the production and economics of bitter leaf.…”
Section: Under-utilized Leafy Vegetables (Ulv)mentioning
confidence: 99%